1639 Va. Acts 228, Act 21 - (:unkn) unknown (General Publisher, 1639)
Not to shoot or hunt on other men’s land that is seated and bounds marked under penalty of 40s. but may pursue deer and shoot on their own land.
--
Keywords: HUNTING REGULATION